Impact of patient information leaflets on doctor–patient communication in the context of acute conditions: a prospective, controlled, before–after study in two French emergency departments. Issue 2 (20th February 2019) - Sustersic, Mélanie; Tissot, Marisa; Tyrant, Julie; Gauchet, Aurelie; Foote, Alison; Vermorel, Céline; Bosson, Jean Luc
Abstract : Objective: In the context of acute conditions seen in an emergency department, where communication may be difficult, patient information leaflets (PILs) could improve doctor–patient communication (DPC) and may have an impact on other outcomes of the consultation. Our objective was to assess the impact of PILs on DPC, patient satisfaction and adherence, and on patient and doctor behaviours. Design: Prospective, controlled, before–after trial between November 2013 and June 2015. Setting: Two French emergency departments. Participants: Adults and adolescents >15 years diagnosed with ankle sprain or an infection (diverticulitis, infectious colitis, pyelonephritis, pneumonia or prostatitis). Intervention: Physicians in the intervention group gave patients a PIL about their condition along with an oral explanation. Main outcome measures: 7–10 days later, patients were contacted by phone to answer questionnaires. Results were derived from questions scored using a 4-point Likert scale. Main findings: Analysis of the 324 patients showed that PILs improved the mean DPC score (range: 13–52), with 46 (42–49) for 168 patients with PILs vs 44 (38-48) for 156 patients without PILs (p<0.01). The adjusted OR for good communication (having a score >35/52) was 2.54 (1.27 to 5.06). The overall satisfaction and adherence scores did not show significant differences. In contrast, satisfaction with healthcare professionals and timing of medication intake were improved with PILs. The overall satisfaction score improved significantly on per-protocol analysis. When using PILs, doctors prescribed fewer drugs and more examinations (radiology, biology, appointment with a specialist); the need for a new medical consultation for the same pathology was reduced from 32.1% to 17.9% (OR 0.46 [0.27 to 0.77]), particularly revisiting the emergency department. Conclusion: In emergency departments, PILs given by doctors improve DPC, increase patients' satisfaction with healthcare professionals, reduce the number of emergency reconsultations for the same pathology and modify the doctor's behaviour. Trial registration number: NCT02246361 .